PEMBELAJARAN METODE DEMONTRASI DAN ALAT PERAGA TERHADAP HASIL BELAJAR PKN SISWA KELAS III SDN 004 TERATAK BULUH KECAMATAN SIAK HULU - Jasmini Jasmini (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This study aims to improve the learning outcomes of PKN by applying learning methods demonstration and teaching aids of third grade students of SDN 004 Teratak Buluh. This research is a classroom action research that includes activities with stages of planning, action, observation, and reflection. The results showed that the increase in student PKN learning outcomes on average students before classroom action research, namely, 66.8 experienced an increase in the first cycle of 76.4 and again increased in the second cycle of 80.4. Based on the results of the study, it can be concluded that by applying the demonstration learning method and the demonstration tool can improve the low PKN learning outcomes of class III SDN 004 Teratak Buluh, District of Siak Hulu, Kampar Regency.